Sonchus asper (L.) Hill extracts: phytochemical characterization and exploitation of its biological activities by loading into nanoformulation - Parisi, Valentina; Santoro, Valentina; Faraone, Immacolata; Benedetto, Nadia; Vassallo, Antonio; De Tommasi, Nunziatina; Milella, Luigi; Nesticò, Antonio; Maselli, Gabriella; Fadda, Anna Maria; Caddeo, Carla (Frontiers in Plant Science, 2024)
The current investigation presents a two-fold approach to rediscovering the potential of Sonchus asper as a wild edible plant, both in its raw extract form and as a nano-formulated product. S. asper is commonly utilized as a food ingredient, and through HPLC-MS analysis of raw and cooked leaf extracts, 38 compounds and 6 essential amino acids were identified. The antioxidant activity and the hypoglycemic effect of non-edible leaves were demonstrated. The incorporation into liposomes maximized the health-promoting properties for potential pharmaceutical or food applications. Furthermore, the study aimed to promote the valorization of traditional dishes, and contribute to biodiversity conservation and sustainable use of S. asper, thus enhancing economic profits. In this regard, the commercialization of S. asper could: (i) contribute to improving the well-being of rural and urban communities, being S. asper a wild edible plant available at low cost, environmentally friendly, resilient, and adaptable; (ii) generate landowner economic returns.